1998
DOI: 10.2307/1602628
|View full text |Cite
|
Sign up to set email alerts
|

Family-Centered Services: Approaches and Effectiveness

Abstract: Much of the emphasis in the nation's system of child protection focuses on investigations to determine whether child abuse or neglect has occurred, and procedures for arranging out-of-home care for children who are not safe at home. Less attention often goes to the capacity of public and private agencies to provide services that help stressed families prevent child maltreatment before it begins, or that enable families with serious child-rearing problems to stabilize the home and provide more appropriate care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 18 publications
0
23
0
5
Order By: Relevance
“…Evaluations of family support programmes elsewhere suggest that the effects are modest and inconsistent (McCroskey & Meezan, 1998). Some show improved child outcomes, others positive effects on parents, but few findings appear consistently across evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluations of family support programmes elsewhere suggest that the effects are modest and inconsistent (McCroskey & Meezan, 1998). Some show improved child outcomes, others positive effects on parents, but few findings appear consistently across evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Cox (1997Cox ( , 1998 and McCroskey and Meezan (1998) conclude that home visiting programmes have not been found to prevent child maltreatment, as measured in official reports, although some programmes modified aspects of parenting that are thought to influence maltreatment. Ayoub and Willett (1992) studied the effects of family preservation for 100 families referred for incidents of maltreatment, and found that treatment was most successful for situationally and chronically stressed families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policy directives indicate that non-governmental organisations (NGOs) should be aimed at reducing child abuse and neglect while protecting the child and preserving the family unit (Ministry for Welfare and Population Development, 1997). Child protection services are focused on family-centred interventions, referred to in the literature as "family support services" and "family preservation services" (Katz & Hetherington, 2006;McCowskey & Meezan, 1998;Statham, 2000).…”
Section: Social Development and Child Welfare Servicesmentioning
confidence: 99%
“…Globally the numbers of children being exposed to child abuse and neglect have increased (Adams, 2005;Watson, 2005), yet family welfare organisations are finding themselves under-resourced and unable to meet this demand for services (DePanfilis & Zuravin, 2002;McCowskey & Meezan, 1998). In South Africa inadequate human resources and the growing demand for child protection services have had a profound effect on the professional practice of social workers, posing critical challenges to them in achieving both the goals of social work and the democratic ideals of the country (Abdullah, 2013:2).…”
Section: Social Development and Child Welfare Servicesmentioning
confidence: 99%